Superfast laser cooling. - Machnes, S; Plenio, M; Reznik, B; Steane, A; Retzker, A (2010)
Currently, laser cooling schemes are fundamentally based on the weak coupling regime. This requirement sets the trap frequency as an upper bound to the cooling rate. In this work we present a numerical study that shows the feasibility of cooling in the strong-coupling regime which then allows cooling rates that are faster than the trap frequency with experimentally feasible parameters. The scheme presented here can be applied to trapped atoms or ions as well as to mechanical oscillators. It can also cool medium sized ion chains close to the ground state.